Do intra-forest meadows influence browsing pressure on tree seedlings? A case study on silver fir, spruce and beech - Anthony Bled; Clément Calenge; Catherine Collet; Vincent Boulanger; Sonia Saïd (Forest Ecology and Management, 2026)

Toll-like Receptor 3 is Required for Sensing Extracellular Double Stranded RNA in Salmonid Cells - Bertrand Collet; Catherine Collins; Mathilde Peruzzi; Justine Catherine-Mezeray; Stephanie DeWitte-Orr; Alexander Rebl; Pierre Boudinot (Marine Biotechnology, 2026)

Disruption of Myd88 in a salmonid epithelioid cell line reveals its contribution to bacterial detection and immune response - Alexander Rebl; Mathilde Peruzzi; Catherine Collins; Niccolò Vendramin; Pierre Boudinot; Niels Lorenzen; Bertrand Collet (Cell and Tissue Research, 2025)

Corrigendum to “Oak regeneration facing deer browsing: Can competition between saplings offset the diversion effect? A simulation experiment” [Ecological Modelling 489 (2024) 110608] - Julien Barrere; Gauthier Ligot; Vincent Boulanger; Catherine Collet; Benoit Courbaud; François de Coligny; Anders Mårell; Sonia Saïd; Philippe Balandier (Ecological Modelling, 2025)

Mechanical site preparation severity mediates one-year-survival response to summer drought in planted tree seedlings - Catherine Collet; Chloé Agro; Emila Akroume; Jordan Bello; Alain Berthelot; Vincent Boulanger; Aurore Calas; Noé Dumas; Jonathan Pitaud; Malaurie Puyal; Florian Vast (New Forests, 2024)

Oak regeneration facing deer browsing: Can competition between saplings offset the diversion effect? A simulation experiment - Julien Barrere; Gauthier Ligot; Vincent Boulanger; Catherine Collet; Benoît Courbaud; François de Coligny; Anders Mårell; Sonia Saïd; Philippe Balandier (Ecological Modelling, 2024)

Monitoring and control of forest seedling quality in Europe - Milan Mataruga; Branislav Cvjetković; Bart De Cuyper; Ina Aneva; Petar Zhelev; Pavel Cudlín; Marek Metslaid; Ville Kankaanhuhta; Catherine Collet; Peter Annighöfer; Thomas Mathes; Tsakaldimi Marianthi; et al. (Forest Ecology and Management, 2023)

Climatic water availability modifies tree functional diversity effects on soil organic carbon storage in European forests - Richard Osei; Hugues Titeux; Miren del Río; Ricardo Ruiz-Peinado; Kamil Bielak; Felipe Bravo; Catherine Collet; Corentin Cools; Jean-Thomas Cornelis; Lars Drössler; Michael Heym; Nathalie Korboulewsky; et al. (European Journal of Forest Research, 2023)

The distribution of carbon stocks between tree woody biomass and soil differs between Scots pine and broadleaved species (beech, oak) in European forests - Richard Osei; Miren del Río; Ricardo Ruiz-Peinado; Hugues Titeux; Kamil Bielak; Felipe Bravo; Catherine Collet; Corentin Cools; Jean-Thomas Cornelis; Lars Drössler; Michael Heym; Nathalie Korboulewsky; et al. (European Journal of Forest Research, 2022)

Plasmid-driven RNA interference in fish cell lines - Bertrand Collet; Catherine Collins; Vivienne Cheyne; Katherine Lester (In Vitro Cellular & Developmental Biology - Animal, 2022)

Cultivation profile: a visual evaluation method of soil structure adapted to the analysis of the impacts of mechanical site preparation in forest plantations - Catherine Collet; Florian Vast; Claudine Richter; Rémi Koller (European Journal of Forest Research, 2021)

Effects of different site preparation methods on the root development of planted Quercus petraea and Pinus nigra - Mathieu Dassot; Catherine Collet (New Forests, 2021)

Windstorm‐induced canopy openings accelerate temperate forest adaptation to global warming - Lucie Dietz; Catherine Collet; Jean‐Luc Dupouey; Eric Lacombe; Lisa Laurent; Jean‐Claude Gégout (Global Ecology and Biogeography, 2020)
Aim Climate change is known to be a driver of changes in forest plant communities and to modify disturbance regimes. We investigated whether forest gaps favoured vegetation adaptation to warmer climates by accelerating the shift of plant communities to a warmer‐adapted composition independently of canopy closure linked to natural forest dynamics. Location Temperate and mountainous forests of France. Time period 2002–2018. Major taxa studied Vascular plants. Methods Using floristic surveys conducted in 2002 and 2018 in 139 permanent plots set up in unmanaged forest gaps created by windstorms in 1999, we assessed the plant communities’ changes in context of global warming. We also compared gap communities to closed communities inventoried in undisturbed forest. A community temperature index (CTI) and a community light index (CLI) were computed for each floristic survey with species temperature optima and Ellenberg light indicator values, respectively. Results CTI increased significantly in the gaps over the 16 years by 0.11°C/decade on average. During the same period, the CLI decreased, indicating that community thermophilization was not the direct result of an increase in solar radiation linked to gap creation. Models showed that, after canopy recovery, thermophilization was stronger in mountains (+0.54°C) than lowland sites (+0.12°C) compared to undisturbed forests. The difference between former gaps and undisturbed forests resulted from the colonization of warm adapted species and the decline of cold adapted species in gaps. Main conclusions For a given canopy closure, our results show that thermophilization of understorey communities is higher in areas with previous disturbances than in undisturbed forests. By increasing the speed of thermophilization, the disturbance regime plays a key role in the adaptation of forest communities to climate warming. The effects of large‐scale disturbances on forest plant composition should therefore not be overlooked, especially since disturbance regime tends to intensify with climate change.

Time shifts in height and diameter growth allocation in understory European beech (Fagus sylvatica L.) following canopy release - Estelle Noyer; François Ningre; Jana Dlouhá; Mériem Fournier; Catherine Collet (Trees, 2019)

Aboveground overyielding in a mixed temperate forest is not explained by belowground processes - Alexandre Fruleux; Marie-Béatrice Bogeat-Triboulot; Catherine Collet; Aurélie Deveau; Laurent Saint-André; Philippe Santenoise; Damien Bonal (Oecologia, 2018)

Effects of repeated anaesthesia on gill and general health of Atlantic salmon, Salmo salar - Rachel J. Chance; Gary A. Cameron; Mark Fordyce; Patricia Noguera; Tiehui Wang; Catherine Collins; Christopher J. Secombes; Bertrand Collet (Journal of Fish Biology, 2018)
Fish are the second most widely utilized vertebrate group used for scientific procedures in the United Kingdom, but the development and application of 3Rs (the principles of replacement, reduction, and refinement) in aquaculture disease research lags behind methodologies in place for mammalian studies. With a need for individual monitoring and non‐lethal sampling, the effect of repeat anaesthesia on experimental fish needs to be better understood. This study analyses the effect of repeat anaesthesia with MS‐222, metomidate and AQUI‐S upon the gill and general health of post‐smolt Atlantic salmon Salmo salar . A single, lethal dose of anaesthetic was compared with seven anaesthetizing time points over 28 days, terminating in a lethal dose. No anaesthetic showed significant differences in accumulation in the muscle tissue, or changes in plasma glucose after repeated or single dosing. Fish repeatedly anaesthetized with MS‐222 or AQUI‐S exhibited upregulation of osmoregulatory genes in the gill and AQUI‐S‐treated individuals showed, histologically, epithelial lifting from the lamellae capillary irrespective of whether they had a single or repeated dose history. No significant changes were seen in inflammatory or stress genes in the head kidney of fish repeatedly anaesthetized with AQUI‐S or metomidate, however MS‐222 treatment resulted in upregulation of tnfα3. Repeated anaesthesia with MS‐222 and metomidate gave a significant decrease and increase in peripheral blood neutrophils, respectively. This study concludes that no increase in cumulative stress or inflammation is induced by the repeated anaesthetization of S. salar with any of the tested anaesthetics, however gill osmotic regulation and blood parameters may be affected.

Radial growth resilience of sessile oak after drought is affected by site water status, stand density, and social status - Raphaël Trouvé; Jean-Daniel Bontemps; Catherine Collet; Ingrid Seynave; François Lebourgeois (Trees, 2017)

Species-specific and generic biomass equations for seedlings and saplings of European tree species - Peter Annighöfer; Aitor Ameztegui; Christian Ammer; Philippe Balandier; Norbert Bartsch; Andreas Bolte; Lluís Coll; Catherine Collet; Jörg Ewald; Nico Frischbier; Tsegay Gebereyesus; Josephine Haase; et al. (European Journal of Forest Research, 2016)

Manipulating seed availability, plant competition and litter accumulation by soil preparation and canopy opening to ensure regeneration success in temperate low-mountain forest stands - Mathieu Dassot; Catherine Collet (European Journal of Forest Research, 2015)

Crown responses to neighbor density and species identity in a young mixed deciduous stand - Ignacio Barbeito; Catherine Collet; François Ningre (Trees, 2014)

Estimating light climate in forest with the convex densiometer: operator effect, geometry and relation to diffuse light - Olivier Baudry; Charlotte Charmetant; Catherine Collet; Quentin Ponette (European Journal of Forest Research, 2014)

Stable tumor vessel normalization with pO2 increase and endothelial PTEN activation by inositol trispyrophosphate brings novel tumor treatment - Claudine Kieda; Bouchra El Hafny-Rahbi; Guillaume Collet; Nathalie Lamerant-Fayel; Catherine Grillon; Alan Guichard; Jozef Dulak; Alicja Jozkowicz; Jerzy Kotlinowski; Konstantina C. Fylaktakidou; Aurélien Vidal; Philippe Auzeloux; et al. (Journal of Molecular Medicine, 2013)

Crown plasticity reduces inter-tree competition in a mixed broadleaved forest - Fleur Longuetaud; Alexandre Piboule; Holger Wernsdörfer; Catherine Collet (European Journal of Forest Research, 2013)

When should exotic forest plantation tree species be considered as an invasive threat and how should we treat them? - Marine Dodet; Catherine Collet (Biological Invasions, 2012)

Tree regeneration and plant species diversity responses to vegetation control following a major windthrow in mixed broadleaved stands - Marine Dodet; Catherine Collet; Henri Frochot; Léon Wehrlen (European Journal of Forest Research, 2011)

Root System Development of Oak Seedlings Analysed using an Architectural Model. Effects of Competition with Grass - Catherine Collet; Magnus Löf; Loïc Pagès (Plant and Soil, 2006)

Root Typ: a generic model to depict and analyse the root system architecture - Loïc Pagès; Gilles Vercambre; Jean-Louis Drouet; François Lecompte; Catherine Collet; Jacques Le Bot (Plant and Soil, 2004)